2013
DOI: 10.15171/ijhpm.2013.28
|View full text |Cite
|
Sign up to set email alerts
|

Informal Payments in Healthcare: A Case Study of Kerman Province in Iran

Abstract: Background: Informal payments for health care, which are common in many countries, can have negative effects on health care access, equity and health status as they lead people to forgo or delay seeking care, or to sell assets to pay for care. Many countries are putting reforms in place with the aim of reducing informal payments. In order to be successful, such policies should be informed by the underlying causes of such payments. This study attempts to explore why, how, and in what ways informal payments occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 21 publications
2
58
0
Order By: Relevance
“…21,22 Also, there is evidence of the lack of sustainability of medical specialists in deprived areas, 5 high rate of caesarian sections 23,24 and high amounts of informal payments. 25 Employer-sponsored health insurance systems in Iran were not able to equally protect people from catastrophic payments. 19 On the other hand, previous interventions such as the Urban Inpatient Insurance Scheme (launched in 2000) and the Rural Health Insurance Scheme (launched in 2005) had regressive impacts on the distribution of healthcare financing in Iran.…”
Section: Why This Set Of Programs Was Chosen?mentioning
confidence: 99%
“…21,22 Also, there is evidence of the lack of sustainability of medical specialists in deprived areas, 5 high rate of caesarian sections 23,24 and high amounts of informal payments. 25 Employer-sponsored health insurance systems in Iran were not able to equally protect people from catastrophic payments. 19 On the other hand, previous interventions such as the Urban Inpatient Insurance Scheme (launched in 2000) and the Rural Health Insurance Scheme (launched in 2005) had regressive impacts on the distribution of healthcare financing in Iran.…”
Section: Why This Set Of Programs Was Chosen?mentioning
confidence: 99%
“…This framework consists of five steps of familiarization, identifying a thematic framework, indexing, charting and mapping and interpretation. [11][12] A contact and content summary form was developed for each interview during familiarization process.An initial thematic framework was developed using interviews, prior thoughts. A preliminary framework was developed and then discussed in a series of repetitive sessions between the researchers then the thematic framework was checked against the interviews through repeating the familiarization process, then sections of data were indexed with one or more codes where necessary appropriate, then the coded text was discussed and coding was adjusted where appropriate, this process was repeated several times for all the interviews.…”
Section: -9mentioning
confidence: 99%
“…Evidence indicates that these payments occur in at least 22 African, Asian and European countries (7). Information on the extent of informal payments is negligible due to their illegal nature, but studies have shown that between 10% and 45% of total health expenditures in some low-income countries relates to this type of payment (8). Previous studies in Iran have reported different frequency of informal payments in the health system where amounts of informal payments ranged from 5.93% to 63.8%.…”
Section: Introductionmentioning
confidence: 99%